2002
DOI: 10.1001/archinte.162.3.323
|View full text |Cite
|
Sign up to set email alerts
|

Dilutional Hyponatremia in Patients With Cirrhosis and Ascites

Abstract: Hyponatremia is an alteration in patients with advanced liver disease. Although survival is significantly reduced in patients with spontaneous development of hyponatremia, a reduced sodium concentration cannot be considered as a independent predictor of the risk for death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
1
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(103 citation statements)
references
References 24 publications
3
90
1
7
Order By: Relevance
“…The frequency of serum sodium Յ130 mmol/L in inpatients was 28%, a figure similar to that reported in previous studies including a lower number of patients compared with the current investigation. 3,[16][17][18] Moreover, our study shows that the occurrence of low serum sodium levels is greater than previously reported, because a further 29% of inpatients had a mild reduction in serum sodium levels (between 131 and 135 mmol/L). Corresponding figures in outpatients were 14% and 26%, respectively.…”
Section: Discussioncontrasting
confidence: 49%
“…The frequency of serum sodium Յ130 mmol/L in inpatients was 28%, a figure similar to that reported in previous studies including a lower number of patients compared with the current investigation. 3,[16][17][18] Moreover, our study shows that the occurrence of low serum sodium levels is greater than previously reported, because a further 29% of inpatients had a mild reduction in serum sodium levels (between 131 and 135 mmol/L). Corresponding figures in outpatients were 14% and 26%, respectively.…”
Section: Discussioncontrasting
confidence: 49%
“…Hyponatremia is prevalent in liver cirrhosis and closely associated with hepatorenal syndrome, ascites, encephalopathy, and SBP (Gines et al 1993;Arroyo and Colmenero 2003;Angeli et al 2006;Guevara et al 2009). Hyponatremia has also been reported as a poor prognostic factor in liver cirrhosis and other medical conditions (Borroni et al 2000;Porcel et al 2002;Jenq et al 2010). Recent studies have reported that the nature of the underlying illness as opposed to the severity of hyponatremia can significantly affect the mortality rate associated with hyponatremia (Chawla et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…56 Multiple studies found hyponatremia to be associated with poor prognosis, although multivariate analyses have not uniformly demonstrated its independent association with adverse clinical outcomes. 57 In cirrhosis there is also clear evidence of nonosmotic release of AVP, but as with CHF, the precise contributions of baroreceptor-mediated and other neurohormonal factors have not been clearly established. The portal hypertension associated with cirrhosis provides the stimulus for the splanchnic vasodilatation.…”
Section: S8mentioning
confidence: 99%